2008
DOI: 10.1186/1471-2334-8-35
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immune responses in HIV infected patients with pleural tuberculosis by the QuantiFERON®TB-Gold interferon-gamma assay

Abstract: Background: Diagnosis of tuberculous (TB) pleuritis is difficult and better diagnostic tools are needed. New blood based interferon-gamma (IFN-γ) tests are promising, but sensitivity could be low in HIV positive patients. The IFN-γ tests have not yet been validated for use in pleural fluid, a compartment with higher level of immune activation than in blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 31 publications
2
54
2
1
Order By: Relevance
“…NPV in patients with active tuberculosis 18 articles satisfied our inclusion criteria for evaluating the NPV; 13 assessed the NPV among confirmed tuberculosis cases [22,26,[34][35][36][37][38][39][40][41][42][43][44] and six assessed the prospective outcome in IGRA-negative individuals after an average of 2 yrs [19-22, 45, 46]. Among the studies in which the NPV was evaluated in patients with confirmed tuberculosis (387 tuberculosis cases with a valid T-SPOT1.TB result and 304 with valid QFT-G-IT result), the NPV varied greatly, irrespective of the IGRA used.…”
Section: Specificitymentioning
confidence: 99%
“…NPV in patients with active tuberculosis 18 articles satisfied our inclusion criteria for evaluating the NPV; 13 assessed the NPV among confirmed tuberculosis cases [22,26,[34][35][36][37][38][39][40][41][42][43][44] and six assessed the prospective outcome in IGRA-negative individuals after an average of 2 yrs [19-22, 45, 46]. Among the studies in which the NPV was evaluated in patients with confirmed tuberculosis (387 tuberculosis cases with a valid T-SPOT1.TB result and 304 with valid QFT-G-IT result), the NPV varied greatly, irrespective of the IGRA used.…”
Section: Specificitymentioning
confidence: 99%
“…In the last several months, two case-control studies from high-burden countries (South Africa) and using QFT-TB-GIT have been published [15,16]. Both showed that the QFT-TB-GIT assay had suboptimal sensitivity (27 and 57%, respectively).…”
Section: Pleural Hbha and Ppd Elispot Responsesmentioning
confidence: 99%
“…We therefore hypothesised that TB antigen-specific responses could distinguish active pleural TB from alternative diagnoses and should have better discriminatory value than unstimulated IFN-c, a nonspecific biomarker of inflammation. A recent case-control study from Europe showed a high diagnostic accuracy with the T-SPOT.1TB assay (Oxford Immunotec, Abingdon, UK) [13] but overall data on the utility of two known IFN-c release assays (IGRAs), T-SPOT.1TB and QuantiFERON1-TB Gold In-tube (QFT-TB-GIT; Cellestis, Carnegie, Australia), including a head-to-head comparison, for the diagnosis of TB-PE are limited [13][14][15][16]. There are several other unresolved questions, including the optimal cell number and pleural fluid volume required, optimal cut-off point and utility in high HIV-prevalence settings [17].…”
mentioning
confidence: 99%
“…In another study of 28 patients with pleural TB, results in pleural fluid were inconclusive in 52% of cases, due to high background IFN-γ production. 79 Commercial IFN-γ tests, T-SPOT.TB and QFT-IT in pleural fluid were compared to unstimulated IFN-γ for the diagnosis of pleural TB in 74 patients. 80 In 11 (15%) cases, the cell counts were not large enough to perform the tests.…”
Section: Pleural Tuberculosismentioning
confidence: 99%